2020
DOI: 10.3390/ijms21093261
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the Reactive Oxygen Response Alleviates Experimental Autoimmune Uveitis in Mice

Abstract: Reactive oxygen species (ROS) are produced by host phagocytes and play an important role in antimicrobial actions against various pathogens. Autoimmune uveitis causes blindness and severe visual impairment in humans at all ages worldwide. However, the role of ROS in autoimmune uveitis remains unclear. We used ROS-deficient (Ncf1−/−) mice to investigate the role of ROS in experimental autoimmune uveitis (EAU). Besides, we also used the antioxidant N-acetylcysteine (NAC) treatment to evaluate the effect of suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Reactive-oxygen species (ROS) are produced by enzymatic/nonenzymatic metabolic redox reactions, which can lead to various diseases and disorders, such as uveitis [ 21 ]. In particular, the redox protein thioredoxin (TRX) can produce free radicals, while TXNIP is an endogenous inhibitor of TRX.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive-oxygen species (ROS) are produced by enzymatic/nonenzymatic metabolic redox reactions, which can lead to various diseases and disorders, such as uveitis [ 21 ]. In particular, the redox protein thioredoxin (TRX) can produce free radicals, while TXNIP is an endogenous inhibitor of TRX.…”
Section: Resultsmentioning
confidence: 99%
“…TXNIP was a pivotal endogenous negative regulator of cellular redox balance [ 22 , 63 , 64 ] that was highly expressed in immune cells and played a role in regulating lymphocyte cycle progression and proliferation in the immune system [ 62 , 65 ]. Sheng-Min Hsu, et al have confirmed suppression of the ROS could alleviate EAU [ 21 ]. In addition, melatonin significantly attenuated ROS production in microglia to alleviate EAE [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since ROS activates NF-κB signaling, which modulates gene expression in diverse cellular processes such as innate immune response ( 29 , 30 ), we next determined if NF-κB plays were required for the expression of inflammatory transcription factors in our EAE model. To do this, we co-stained the active form of NF-κB (pNF-κB) with NeuN or CD11b ( Figure 6G ).…”
Section: Resultsmentioning
confidence: 99%
“…The expression of IL-4 is increased when EAU is induced by IRBP peptide 1-20 in CFA. Treating EAU mice with rapamycin or suppressing the reactive oxygen response both reduce the levels of IL-4 and other cytokines related to Th1 and Th17 cells, thus ameliorating EAU [ 59 , 159 ]. Data from a clinical study suggests that the levels of IL-4 increase in serum and AqH of patients with endogenous uveitis and BD, but the levels are relatively low in BD [ 160 ].…”
Section: Interleukin-4mentioning
confidence: 99%